2015
DOI: 10.1542/peds.2014-3920
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Variation in Health Care Utilization by Children With Medical Complexity

Abstract: BACKGROUND: Although children with medical complexity have high health care needs, little is known about the variation in care provided between centers. This information may be particularly useful in identifying opportunities to improve quality and reduce costs. METHODS:We conducted a retrospective population-based observational cohort study using all payer claims databases for children aged 30 days to ,18 years residing in Maine, New Hampshire, and Vermont from 2007 to 2010. We identified hospital-affiliated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…Although some hospital use is inevitable for children with unpredictable and fragile underlying conditions, growing evidence suggests that reducing hospitalizations for CMC is achievable. 3,4 One randomized controlled trial (RCT) revealed nearly 50% reduction in hospitalizations for CMC enrolled in a complex care medical home. 5 Authors of observational studies have found lower CMC-hospital use with care coordination, care planning, and home visitation.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Although some hospital use is inevitable for children with unpredictable and fragile underlying conditions, growing evidence suggests that reducing hospitalizations for CMC is achievable. 3,4 One randomized controlled trial (RCT) revealed nearly 50% reduction in hospitalizations for CMC enrolled in a complex care medical home. 5 Authors of observational studies have found lower CMC-hospital use with care coordination, care planning, and home visitation.…”
Section: What This Study Addsmentioning
confidence: 99%
“…1 Children with multiple complex chronic conditions (MCCs) are recognized as a focus population for improvement in health care systems because they constitute a small fraction of our communities yet represent a disproportionate amount of health care costs and mortality. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Children with MCCs represented more than onequarter of children in the top 5% of Medicaid spending in 2010. 20 In addition, children who are hospitalized with MCCs have a threefold longer hospital length of stay, 11-fold greater charges, and 15-fold higher inpatient mortality compared with children who are hospitalized without MCCs.…”
mentioning
confidence: 99%
“…22,23 Despite the burden of MCCs on children, families, communities, and health care systems, the epidemiological assessment of children with MCCs within a geographically defined pediatric US population has not been previously performed. Although valuable, the extant literature is limited to cohorts derived from databases originating from health care use,* payer source, 4,[7][8][9][10]14,20,[30][31][32][33] death certificates, [34][35][36][37] and national surveys. 38,39 Furthermore, the reported prevalence for chronic disease in children is widely variable (0.2%-44%) because of considerable heterogeneity in study definitions, designs, populations, and conditions.…”
mentioning
confidence: 99%
“…In this issue of Pediatrics, Ralston et al, 4 by using an all payer claims database, examine variation in health care utilization in a population-based cohort of CMC across 4 children's hospitals in New England. This cohort was defined based on revised CCC discharge diagnosis codes 3 further refined to minimize bias by excluding children with disease processes necessitating care at 1 specific hospital (eg, bone marrow transplantation).…”
mentioning
confidence: 99%
“…Ralston and colleagues 4 found high variation in rates of encounters, imaging, and diagnostics among the 4 hospitals: twofold variation in inpatient and intensive care days, threefold variation in head MRI, and fivefold variation in electrocardiography. Key differences in patient characteristics across the hospitals were adjusted for, notably median household income by zip code, percent Medicaid, and CCC diagnostic categorizations.…”
mentioning
confidence: 99%